CONSTRUCTION OF THE ABILITY TO READ THE QUR'AN IN THE ELDERLY IN THE HOUSE OF THE QUR'AN NOBLE MORALS - Yuwana (Archipelago Journal of Southeast Asia Islamic Studies, 2024)
The Qur'an has been revealed as a guidance for the people of the world and the Hereafter. The purpose of reading this Qur'an is to help the elderly who do not understand how to read it. This research aims to find out the forms of construction, the methods used, as well as the supporting and inhibiting factors in the construction of the ability to read the Qur'an at the Senior Centers in the House of the Quran Akhlak Mulia, the village of Sebayan, the district of Sambas. The approach used by the researchers in this study is a descriptive approach. The type of research used is qualitative research. The data sources used are primary and secondary data sources. The following results were obtained from the research carried out: (1) The form of reading the Qur'an at the location of the research is a personality and gives motivation regarding the priority of learning the Quran. (2) There are three methods used in reading the Qur'an at the study site: Wafa, Iqra, and Tilawah. Wafa is used as an early stage in learning the letter, while Iqrah is used to test the early ability of the centurion. If the centurians have difficulty in understanding the Wafa they will be transferred to Iqra so that they can learn the Quran more easily. (3) The supporting factors of the building of the ability to read the Qur'an in the higher age centers in the House of the Quran are as follows: (a). Have good collaboration between core managers, teachers, and the community, (b) a high learning spirit of the elderly, (c) high social spirit. In addition to these supportive factors, obstacles were found, among others: a lack of teachers commitment and weak physical condition of the elderly, hindering the learning process